2006
DOI: 10.1007/s10827-005-3589-4
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-invariant processing and spectrotemporal reverse correlation in primary auditory cortex

Abstract: The spectrotemporal receptive field (STRF) provides a versatile and integrated, spectral and temporal, functional characterization of single cells in primary auditory cortex (AI). In this paper, we explore the origin of, and relationship between, different ways of measuring and analyzing an STRF. We demonstrate that STRFs measured using a spectrotemporally diverse array of broadband stimuli -such as dynamic ripples, spectrotemporally white noise, and temporally orthogonal ripple combinations (TORCs) -are very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 62 publications
1
72
2
Order By: Relevance
“…More importantly, their analysis focused on gross-scale structure of the STRFs, whereas our results suggest that nonlinearities may express themselves in a more subtle manner. The DRC-and ripple-estimated STRFs of Figure 2, e and f, for instance, have a correlation coefficient of 0.83; this contrasts with the mean correlation coefficient of 0.64 for STRFs in the study by Klein et al (2006). Although the STRFs we estimate with DRC and ripple stimuli are well correlated, the differences between them would greatly complicate analysis of receptive field structure.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…More importantly, their analysis focused on gross-scale structure of the STRFs, whereas our results suggest that nonlinearities may express themselves in a more subtle manner. The DRC-and ripple-estimated STRFs of Figure 2, e and f, for instance, have a correlation coefficient of 0.83; this contrasts with the mean correlation coefficient of 0.64 for STRFs in the study by Klein et al (2006). Although the STRFs we estimate with DRC and ripple stimuli are well correlated, the differences between them would greatly complicate analysis of receptive field structure.…”
Section: Discussioncontrasting
confidence: 60%
“…Previously, for example, Klein et al (2006) examined the stability of STRFs estimated for auditory cortical neurons using a variety of stimulus classes and concluded that stimulus dependence of the STRFs was minimal (and therefore that the neuronal response functions could reasonably be described as linear). However, the stimuli they used were all derived from ripple stimuli and may possess similar higher-order statistics.…”
Section: Discussionmentioning
confidence: 99%
“…To explore possible neural mechanisms that could produce noise-robust representation in A1, we simulated neural activity using the spectrotemporal receptive field (STRF), which is commonly used to characterize functional properties of auditory neurons (10,19,20):…”
Section: Reduced Distortions In Stimuli Reconstructed From the A1 Popmentioning
confidence: 99%
“…The reliability of an STRF was measured using a bootstrap technique (Efron and Tibshirani, 1998), which allowed us to quantify the variance of the neural response and hence the overall SNR for each STRF. The bootstrap analysis, as well as SNR measurement procedure, are explained in details by Klein et al (2006). Most SNRs were Ͼ1, and we excluded all STRFs with an SNR Ͻ0.2 from our analysis.…”
Section: Receptive Field Estimationmentioning
confidence: 99%